DHA-enriched phosphatidylcholine from Clupea harengus roes regulates the gut–liver axis to ameliorate high-fat diet-induced non-alcoholic fatty liver disease. Issue 22 (20th October 2022) - Qian, Li; Tian, Shanshan; Jiang, Su; Tang, Yunping; Han, Tao
Abstract : DHA-enriched phosphatidylcholine from Clupea harengus roes could likely be used as a functional food supplement for the prevention of high-fat diet-induced non-alcoholic fatty liver disease via the gut–liver axis. Abstract : In this study, the protective effect of DHA-enriched phosphatidylcholine (DHA-PC) from Clupea harengus roes against high-fat diet (HFD)-induced non-alcoholic fatty liver disease (NAFLD) was investigated. Our results indicated that DHA-PC significantly decreased the murine body weights, liver indexes, serum ALT, AST, and LPS levels, improved the serum lipid levels (TG, TC, LDL-C, HDL-C, NEFA), relieved the hepatic levels of the pro-inflammatory cytokines (IL-6, IL-1β, and TNF-α), and hepatic oxidative stress (MDA, SOD, GSH-Px, and CAT) in mice fed on HFD. DHA-PC significantly decreased protein expression levels of TLR4, MyD88, IKKβ, p-P65, and p-IκBα in the liver and upregulated the protein expression levels of ZO-1, occludin, and claudin-4 in the jejunum. Moreover, DHA-PC treatment alleviated intestinal dysbiosis caused by HFD. At the genus level, DHA-PC promoted the relative abundances of unclassified Muribaculaceae, Lachnospiraceae NK4A136 group, Blautia, and unclassified Clostridia UCG-014, while reducing the abundance of Allobaculum, unclassified Atopobiaceae, Alistipes, Faecalibaculum, Lachnoclostridium, and Tuzzerella . Our findings suggest that DHA-PC alleviated HFD-induced NAFLD by regulating lipid metabolism and dysbiosis via the gut–liver axis.